(untitled) (The Review of Diabetic Studies, 2025)
Multi-departmental collaboration has become a cornerstone of modern healthcare transformation, offering a structured approach to bridging clinical, diagnostic, administrative, and supportive functions to enhance patient outcomes. As patient needs grow more complex, isolated departmental efforts are no longer sufficient to deliver safe, efficient, and person-centered care. This comprehensive review synthesizes evidence from 2016–2025 to examine how multi-departmental integration enhances clinical performance, operational efficiency, and patient-centered results across diverse healthcare settings. The findings reveal that coordinated collaboration among departments—such as nursing, pharmacy, laboratory services, radiology, rehabilitation, emergency medicine, and health information management—significantly improves diagnostic accuracy, reduces treatment delays, strengthens medication safety, and enhances continuity across care transitions. Operationally, collaboration optimizes workflows, decreases duplication of services, improves resource utilization, and reduces the length of hospital stay. Patient-centered outcomes also improve through better communication, enhanced satisfaction, reduced anxiety, and more personalized care delivery. Despite measurable benefits, challenges related to organizational culture, communication barriers, digital interoperability, and leadership gaps persist. The review concludes that multi-departmental collaboration is an essential driver for achieving high-reliability healthcare systems and represents a transformative strategy for maximizing patient outcomes within value-based care models.